The web portal of the EUROSEISTEST strong ground motion database. - Pitilakis, K.; Roumelioti, Z.; Manakou, M.; Raptakis, D.; Liakakis, K.; Anastasiadis, A.; Pitilakis, D. (Bulletin of the Geological Society of Greece, 2013)
Strong motion data that have been recorded during the 20-years of operation of the permanent network of EUROSEISTEST (Mygdonia basin, Northern Greece) have been homogenized and organized in an easily accessible, via the web, database. The EUROSEISTEST web portal and the application server running underneath are based solely on free and open source software (F/OSS; MySQL v5.5; RubyOnRails, SAC, Gnuplot and numerous GNU supporting utilities). Its interface allows the user to easily search strong motion data from approximately 200 events and 26 strong motion stations using event-related, record-related or station-related criteria. Further investigation of the data is possible in a graphical environment which includes plots of processed and unprocessed acceleration waveforms, velocity and displacement time histories, amplitude Fourier and response spectra and spectrograms. A great effort was directed toward the inclusion of accurate and most updated earthquake metadata, as well as a wealth of stations related information such as geotechnical and geophysical site characterization measurements, subsoil structure and site effects. Acceleration data can be easily downloaded in either SAC or ASCII format, while all stations metadata are also available to download.